Abbreviated dual antiplatelet therapy in patients undergoing percutaneous coronary intervention: a systematic review and meta-analysis of randomized controlled trials - Hamidreza Soleimani; Elaheh Karimi; Mehrdad Mahalleh; Fatemeh Jodeiri Entezari; Ali Nasrollahizadeh; Amir Nasrollahizadeh; Hamed Rafiee; Parvin Kalhor; Karim M. Al-Azizi; Luis H. Paz Rios; Wilbert S. Aronow; Andrew P. Ambrosy; et al. (BMC Cardiovascular Disorders)
Abstract Background Dual antiplatelet therapy (DAPT), combining aspirin and a P2Y12 receptor inhibitor, is a standard post-percutaneous coronary intervention (PCI) treatment to reduce thrombosis and ischemic events. However, the optimal DAPT duration remains unclear, with concerns about bleeding risks associated with long-term potent P2Y12 inhibitors. This systematic review and meta-analysis investigates the safety and efficacy of shortened DAPT regimens. Methods A comprehensive search of PubMed, Scopus, and EMBASE identified randomized controlled trials (RCTs) comparing conventional DAPT (≥ 12 months) and abbreviated DAPT (≤ 3 months) post-PCI. Primary outcomes were 1-year all-cause mortality and bleeding, assessed using the Bleeding Academic Research Consortium (BARC) classification. Secondary outcomes included cardiovascular mortality, non-fatal myocardial infarction (MI), stroke, and major adverse cardiovascular events (MACE). Risk of bias was assessed with the Cochrane tool, and meta-analyses used random-effects models. Results Forty studies involving 54,233 participants were included. Abbreviated DAPT significantly reduced all-cause mortality (RR: 0.90, 95%CI: 0.82–0.98) and bleeding (BARC 3 or 5: RR: 0.77, 95%CI: 0.60–0.97). No significant differences were observed in cardiovascular mortality, stroke, non-fatal MI, revascularization, or in-stent thrombosis. Subgroup analyses showed lower mortality with 1-month DAPT and reduced bleeding in patients with high bleeding risk, acute coronary syndrome (ACS), and complex PCI. Conclusions Abbreviated DAPT post-PCI is associated with lower all-cause mortality and bleeding without compromising ischemic protection, supporting its use in specific patient populations. Individualized DAPT durations should be considered to balance bleeding and ischemic risks.